Crack Healing Mechanism by Application of Stack Pressure to the Carbon-Based Composite Anode of an All-Solid-State Battery - Lee, HyunJeong; Kim, Hae Ryoung; KYUJOON LEE; YEBIN LEE; Kim, Hong-Kyu; Yoon, Woo-Young; Ahn, Jae Pyoung (AMER CHEMICAL SOC, 2022)
Mechanical cracks in an all-solid-state battery (ASSB) disrupt lithium-ion conduction pathways; thus, strategies to overcome these are warranted. We found that the stack pressure during charging and discharging heals microcracks in ASSBs, which imparts long-term cyclability in a composite anode made of graphite and solid-state electrolyte (SE, Li6PS5(Cl,Br)). The microcracks were generated when a fabrication pressure of 400 MPa was released but were mechanically bonded under a stack so i pressure of 40 MPa during cycle tests. They healed further due to the formation of a solid electrolyte interface (SEI) at the binder layer with a thickness of approximately 100 nm between the Cycle number mechanically contacted graphite and SE. In this crack healing process, the binder served as medium for the movement of Li, S, and O atoms and as the location for the amorphous SEI layer formation. The SEI layer was primarily similar to that of lithium carbonate (Li2CO3), which contained small amounts of sulfur, in terms of the chemical composition and chemical bond. The binder in the ASSB changed to a lithium carbonate SEI regardless of the stack pressure. In the absence of the stack pressure, the ASSB cells maintained the initial structure of the binder and crack in the pristine cell and were degraded with the crucial expansion of the microcracks between electrode materials. The stack pressure was most effective in mitigating the capacity reduction of ASSBs because it induced mechanical and chemical crack healing, which restored the conduction pathways between the graphite and SE particles. The mechanical and structural understanding acquired in this study is expected to provide research angles for sustainable, cost-effective, and high-performance graphite/argyrodite-based ASSB design and fabrication.